A molecular approach to understanding the role of diet in cancer-telated fatigue: challenges and future opportunities - Crowder, Sylvia L.; Playdon, Mary C.; Gudenkauf, Lisa M.; Ose, Jennifer; Gigić, Biljana; Greathouse, Leigh; Peoples, Anita R.; Sleight, Alix G.; Jim, Heather S. L.; Figueiredo, Jane C. (Nutrients, 2022)
Cancer-related fatigue (CRF) is considered one of the most frequent and distressing symptoms for cancer survivors. Despite its high prevalence, factors that predispose, precipitate, and perpetuate CRF are poorly understood. Emerging research focuses on cancer and treatment-related nutritional complications, changes in body composition, and nutritional deficiencies that can compound CRF. Nutritional metabolomics, the novel study of diet-related metabolites in cells, tissues, and biofluids, offers a promising tool to further address these research gaps. In this position paper, we examine CRF risk factors, summarize metabolomics studies of CRF, outline dietary recommendations for the prevention and management of CRF in cancer survivorship, and identify knowledge gaps and challenges in applying nutritional metabolomics to understand dietary contributions to CRF over the cancer survivorship trajectory.